Adapted milk formulas for newborns - Momcilovic, Ana (PONS - medicinski časopis, 2026)
Breastfeeding is the best and most natural way of feeding newborns, but there are factors that make breastfeeding difficult or completely impossible for either the child or the mother. In those cases, adapted milk is used, which is the most similar to the composition of mother's milk in terms of quality and quantity of nutrients. The aim of this work is to examine the reasons for using and choosing adapted milk formulas. The choice of adapted milk formula depends on the age of the newborn, his health condition, as well as individual specifics. There is no universal way of choosing, but special attention should be paid to formulas, which are intended for newborns with different health conditions or nutritional challenges.
Keywords: newborn, breastfeeding, milk, nutrients